An investigation into the pyrolysis and oxidation of bio-oil from sugarcane bagasse: Kinetics and evolved gases using TGA-FTIR. Issue 5 (October 2021) - Ordonez-Loza, Javier; Chejne, Farid; Jameel, Abdul Gani Abdul; Telalovic, Selvedin; Arrieta, Andrés Amell; Sarathy, S. Mani
Abstract: Bio-oil produced from the pyrolysis of sugarcane bagasse has the potential to be used as a sustainable and renewable energy source. In the present study, a non-isothermal thermo-gravimetric analysis (TGA) of the pyrolysis (in N2 atmosphere) and combustion (in the air) of bio-oil from sugarcane bagasse was investigated at three heating rates: 5, 10, and 20 °C/min. The sample was heated from room temperature up to 900 °C and the evolved gases in the TG furnace were carried to a Fourier transform infrared (FTIR) cell where the composition of the gases and the functional groups present there were analyzed. A global kinetic analysis was performed to obtain the Arrhenius kinetic parameters for the pyrolysis and oxidation of the bio-oil using the distributed activation energy model. Three distinct stages, namely; low-temperature oxidation (LTO), fuel decomposition (FD), and high-temperature oxidation (HTO) were observed during the oxidation of bio-oil. The initial devolatilization of the oxygenated compounds observed during pyrolysis was similar to the LTO stage observed during combustion. The intensity of the CO2 FTIR peaks seen during the bio-oil combustion was 10 times the intensity of the CO2 peaks attained during pyrolysis. The TGA-FTIR analysis of the sugarcane bagasse bio-oil sheds new light on its thermal degradation/oxidation characteristics. Graphical Abstract: ga1 Highlights: Three stages were identified during biooil oxidation. The gases released during oxidation were measured with FTIR. During pyrolysis the formation of char was identified. The char formed was oxidized and its decomposition was characterized.